2022
DOI: 10.3389/fmed.2022.727103
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Fluid Balance in the First Week Was Associated With Increased Long-Term Mortality in Critically Ill Patients: A Retrospective Cohort Study

Abstract: IntroductionEarly fluid balance has been found to affect short-term mortality in critically ill patients; however, there is little knowledge regarding the association between early cumulative fluid balance (CFB) and long-term mortality. This study aims to determine the distinct association between CFB day 1–3 (CFB 1–3) and day 4–7 (CFB 4–7) and long-term mortality in critically ill patients.Patients and MethodsThis study was conducted at Taichung Veterans General Hospital, a tertiary care referral center in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Another explanation for this effect could be the more inferior kidney function in critically ill patients, leading to acute kidney injury with subsequent fluid overload [ 51 , 52 ]. It is known that a higher fluid balance is associated with a more severe medical condition and an increased risk of mortality [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for this effect could be the more inferior kidney function in critically ill patients, leading to acute kidney injury with subsequent fluid overload [ 51 , 52 ]. It is known that a higher fluid balance is associated with a more severe medical condition and an increased risk of mortality [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we are to our knowledge the first study to show the association of early fluid overload with poor long-term clinical outcomes at 1-year in pediatric heart transplant recipients, suggesting a possible pathophysiologic relationship that extends beyond the immediate perioperative period. ICU-related studies have shown an independent relationship between cumulative fluid balance and long-term mortality among critically ill patients [33,34]. Mechanistic studies have suggested prolonged fluid overload can lead to direct adverse effects that are inclusive of microvascular injury associated with tissue edema, endothelial dysfunction and shedding of the endothelial glycocalyx, and dysregulated immunity [4,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The critical care database at TCVGH was utilized to obtain essential clinical data, including demographic details, laboratory results, comorbidities evaluated using the modified Charlson Comorbidity Index (CCI), 17 Acute Physiology and Chronic Health Evaluation (APACHE) II score, presence of septic shock that was defined by diagnosis of sepsis, serum lactate level greater than 18.0 mg/dL as well as usage of vasopressors, receiving mechanical ventilation for more than 3 days, underwent renal replacement therapy, receiving blood transfusion during ICU admission, and cumulative fluid balance status during day 1–3, which have been identified as mortality-relevant factors in our previous investigation and other studies. 18 , 19 We also included the main organ dysfunction/failure as the covariate.…”
Section: Methodsmentioning
confidence: 99%